2008
DOI: 10.1007/s00223-008-9112-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Osteogenic Ability of Rat Mesenchymal Stem Cells from Bone Marrow, Periosteum, and Adipose Tissue

Abstract: Mesenchymal stem cells (MSCs) reside in many types of tissue and are able to differentiate into various functional cells including osteoblasts. Recently, adipose tissue-derived MSCs (AMSCs) have been shown to differentiate into many lineages, and they are considered a source for tissue regeneration. The purpose of this study was to compare the osteogenic differentiation capability of MSCs from bone marrow (BMSCs), MSCs from periosteum (PMSCs), and AMSCs using in vitro culture and in vivo implantation experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(166 citation statements)
references
References 41 publications
11
152
0
1
Order By: Relevance
“…In a previous study, PDC-COl showed hundred times more bone in central area of rat calvaria critical-size defects (rcCsD) in comparison with the control group (5). PDC-hA implanted in subcutaneous tissue induced heterotopic ossification (4).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a previous study, PDC-COl showed hundred times more bone in central area of rat calvaria critical-size defects (rcCsD) in comparison with the control group (5). PDC-hA implanted in subcutaneous tissue induced heterotopic ossification (4).…”
Section: Introductionmentioning
confidence: 91%
“…Periosteum-derived cells (PDC) have osteogenic potential (2)(3)(4)(5). They are an alternative cell source in comparison with bone marrow in the tissue engineering field since they require less invasive and safer techniques by collagen (COl), biocompatible (6), biodegradable and allow adhesion, growing and cellular differentiation (7).…”
Section: Introductionmentioning
confidence: 99%
“…As one example, in rats, A-MSCs have a significantly lower ALP activity per DNA than BM-MSCs and P-MSCs, and osteocalcin levels follow the same trend. 16 When A-MSCs were implanted in muscle, ectopic bone formed at the site, but it was less than that formed with BM-MSCs or P-MSCs. This group concluded that A-MSCs show low endogenous osteoblast differentiation in vivo, but instead recruit other cells that increased bone formation.…”
Section: Discussion Of Findings and Relevant Literature Mesenchymal Smentioning
confidence: 99%
“…Other questions remain including whether the origin of the MSCs may modify the osteosarcoma cells behavior and change outcome. Bone-marrow-derived MSCs are widely used in bone regeneration approaches, and several authors postulate that periosteum may contain MSC populations more suitable for bone tissue engineering purposes [1,8,12,13].…”
Section: How Do We Get There?mentioning
confidence: 99%